Influencia de la sombra y encalado sobre la productividad del cacao (Theobroma cacao L) clon EETP-800, en la Estación Experimental El Padmi, Zamora Chinchipe, - Cobos Ruiz, Klever Patricio (2023)
The cocoa crop (Theobroma cacao L) is very important for the national economy, and the Ecuadorian Amazon is representative in the cocoa crop; however, the acid soils of this region limit the availability and absorption of nutrients. Therefore, in the present study, the effect of the use of shade and liming on productive and soil variables was evaluated. The trial was conducted at the El Padmi Experimental Farm of the National University of Loja, where a completely randomized design with a bifactorial arrangement (shade and liming) was established, with 4 treatments and 4 replications. Crown diameter, fruit length, number of fruits/plants, estimated yield, fruit weight, electrical conductivity and soil pH, SPAD index and leaf area index were evaluated. Crown diameter, number of fruits/plants, estimated yield, electrical conductivity, pH, and SPAD chlorophyll concentration were affected by the interaction between shade and liming. The effect of treatments on the variables was evaluated by ANOVA and Tukey's test (p<0.05). The results show that the crown diameter averaged 140 cm to 190 cm in the control treatment, the number of fruits per plant was obtained in the control and with shade with lime (average of 10 to 14 fruits), the estimated yield (averages of 0.28 t/ha and 0.25 t/ha) in the treatments with lime (average of 10 to 14 fruits), and the estimated yield (averages of 0.28 t/ha and 0.25 t/ha) in the treatments with lime, 25 t/ha) in the control and treatments without shade with lime, electrical conductivity was higher at 84 days (averages 0.15 to 0.21 m3/cm) with the treatment with shade with lime being the highest, and chlorophyll concentration was higher in the first days of evaluation (averages 52 to 60) in the treatment with shade without lime. In contrast, fruit length, ear weight and leaf area index were significantly influenced by the separate factors (p<0.05), with the shade type factor having the best results. The results of this work show that shade is not indispensable in the cocoa production stage, but with regard to liming, this did have an effect since it improved the soil pH and therefore increased the availability of nutrients. Key words: Theobroma cacao L, shade, liming, yield.